2012
DOI: 10.3174/ajnr.a3361
|View full text |Cite
|
Sign up to set email alerts
|

Angioarchitecture of Brain AVM Determines the Presentation with Seizures: Proposed Scoring System

Abstract: BACKGROUND AND PURPOSE:Seizures are a common presentation in patients with brain arteriovenous malformations, but the pathogenesis of seizures remains poorly understood. The purpose of our study was to analyze various morphologic and hemodynamic characteristics of unruptured BAVMs presenting primarily with seizures and, on the basis of these, to propose a scoring system to predict seizures in patients with BAVMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 28 publications
3
20
0
3
Order By: Relevance
“…19 More recently, Shankar et al found a statistically significant association between seizures and AVMs with characteristics of high flow (including pial recruitment and perinidal angiogenesis, fistulization, and intranidal aneurysm) and venous outflow obstruction (including venous ectasia, pial long draining vein, venous outflow restriction draining vein, and pseudophlebitic cortical vein pattern). 16 The mechanism by which SRS leads to a reduction in seizures has not been fully elucidated. Improved cerebral hemodynamics following radiosurgical obliteration may contribute to control of seizures and other adverse symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…19 More recently, Shankar et al found a statistically significant association between seizures and AVMs with characteristics of high flow (including pial recruitment and perinidal angiogenesis, fistulization, and intranidal aneurysm) and venous outflow obstruction (including venous ectasia, pial long draining vein, venous outflow restriction draining vein, and pseudophlebitic cortical vein pattern). 16 The mechanism by which SRS leads to a reduction in seizures has not been fully elucidated. Improved cerebral hemodynamics following radiosurgical obliteration may contribute to control of seizures and other adverse symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al , in a study of 45 patients, found both compact AVM morphology and frontal or temporal location were associated with seizures, but again this study did not examine cross-sectional imaging findings 23. Finally, an analysis of angiographic features of AVMs by Shankar et al noted that a long pial course of a draining vein, fistulous component in the nidus, AVM location, and stenosis of the venous outflow correlated with seizures 24. The results of our study had some findings similar to, and some contradictory to, prior studies: younger patient age and larger AVM size were associated with seizures similar to the report of Hoh et al and a long draining vein was associated with seizures as Sun et al reported, but temporal lobe location was not associated with seizures as had been found by Hoh et al and Sun et al 22 23…”
Section: Discussionmentioning
confidence: 99%
“…The amount of tissue impaired depends on the length and course of the draining vein. If an epileptogenic area of brain is included in this territory, the patient will probably have a higher risk of seizure 24. Short draining veins might have little effect on venous drainage of normal parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Hol et al studied clinical predictors of seizure incidence and seizure outcomes in bAVMs patients with seizure and observed that male sex, age less than 65 years, bAVMs size greater than 3 cm, and bAVMs location in the temporal lobe are associated with pretreatment seizure [ 16 ]. Shankar et al analyzed angioarchitectural characteristics of unruptured bAVMs in a consecutive series of patients presenting with seizures and proposed that venous outflow stenosis, long pial draining vein and location of bAVMs are the strongest predictors of seizures [ 17 ]. A recent prospective study investigating seizures as the initial presentation of bAVMs found that predisposing factors include male sex, increasing bAVMs size, superficial venous drainage, and location in the frontal lobe and arterial border-zone [ 18 ].…”
Section: Discussionmentioning
confidence: 99%